Transmission electron microscopy of Ledderhose disease in a patient with bilateral presentation - A. Merolli; L. Rocchi (Elsevier, 2021)
The plantar fibromatosis of the foot, also known as Ledderhose Disease, presents itself as one or more rounded, firm, hard nodules, typically located on the medial side of the plantar vault. The etiology is unknown but Ledderhose Disease is correlated with the Dupytren contracture and Peyronie's Disease, as they are all fibroproliferative disorders. The lack of significant literature for Transmission Electron Microscopy (TEM) of Ledderhose Disease, prompted us to perform an extensive TEM analysis in a case of bilateral presentation, in a Caucasian male of 31 years of age. We confirmed the morphological similarities among these three diseases. A highly disordered assembly of collagen fibers was documented together with the morphological characters of myofibroblasts for the cell population. Presence of giant cells and possibly mast-cells was notable, but their role and relevance are matter for speculation because of the allergic diathesis of the patient. The specific history of the patient seems to exclude that a recurrent external mechanical stress was the causative action, because it was applied only on one side in an otherwise bilateral presentation. A recommendation is made to every clinician to be aware of Ledderhose Disease and to provide an early diagnosis. In case surgery is required, it should be an accurate micro-surgical excision to be performed in a qualified center.